Аналіз і синтез перфектних форм англійського дієслова активного стану - Ерреро Бікус, Н. (Лексикографічний бюлетень, 2006)
The paper focuses on the creation rules of perfect forms for determining paradigmatic
classes of English verbs. The material is based on the English-Ukrainian dictionary of the
second level provided by the Computational Linguistics laboratory. Had been used the
paradigm of English verb, the created program characterizes with division word-change forms into paradigmatic classes of regular (12) and irregular verbs (56). It encapsulates the automatic analysis of perfect forms in the input text and the automatic synthesis of verbs had been taken into account main methods of verb expression.